2019
DOI: 10.1016/j.ijrobp.2019.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional Observational Study of Prophylactic Extended-Field Concurrent Chemoradiation Therapy Using Weekly Cisplatin for Patients With Pelvic Node-Positive Cervical Cancer in East and Southeast Asia

Abstract: Uterine cervical cancer is among the most common cancers in East and Southeast Asia, and it is necessary to develop new treatment methods suitable for developing countries. This multiinstitutional observational study conducted among 11 East and Southeast Asian countries aimed to evaluate the clinical outcomes of prophylactic extended-field concurrent chemoradiation therapy with locally advanced cervical cancer. The results indicated that extended-field concurrent chemoradiation therapy is feasible and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although several studies have investigated the efficacy of prophylactic para-aortic irradiation for advanced stage cervical cancer [ 26 31 ], the value of prophylactic para-aortic irradiation remains controversial. Some studies claimed that prophylactic para-aortic irradiation improves survival and reduces the risk of recurrence [ 26 28 ], whereas the results from other studies supported contrary claims: prophylactic para-aortic irradiation does not reduce the risk of recurrence for patients with advanced-stage cervical carcinoma [ 29 31 ]. No randomized controlled study has explored the value of prophylactic para-aortic irradiation for treating ASC.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the efficacy of prophylactic para-aortic irradiation for advanced stage cervical cancer [ 26 31 ], the value of prophylactic para-aortic irradiation remains controversial. Some studies claimed that prophylactic para-aortic irradiation improves survival and reduces the risk of recurrence [ 26 28 ], whereas the results from other studies supported contrary claims: prophylactic para-aortic irradiation does not reduce the risk of recurrence for patients with advanced-stage cervical carcinoma [ 29 31 ]. No randomized controlled study has explored the value of prophylactic para-aortic irradiation for treating ASC.…”
Section: Discussionmentioning
confidence: 99%
“…Acute grade 3 leukopenia was observed in 20 patients (21%), and late grade 3 gastrointestinal toxicity was observed in 3%. The results showed that the delayed prophylactic paraaortic radiotherapy decreased the rate of distant metastases and improved PFS and OS rates, without increasing toxicity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrast, some studies indicated that prophylactic EFI did not reduce the risk of para‐aortic nodal recurrence and confer survival benefits in patients with positive pelvic lymph node cervical cancer 10,11 . Anyway, prophylactic EFI is considered to be safe in modern radiotherapy techniques without a significant increase in severe toxicities in patients with cervical cancer 11–13 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Anyway, prophylactic EFI is considered to be safe in modern radiotherapy techniques without a significant increase in severe toxicities in patients with cervical cancer. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%